Using Community Detection in Adolescent Media Multitasking Research. An Exploratory Study - ROGOBETE, Doris Antonia; MURSA, Bogdan Mădălin; IONESCU, Thea; MICLEA, Mircea (Studia Universitatis Babeș-Bolyai Psychologia-Paedagogia, 2025)
In this exploratory study, we used the community detection approach to complex networks analysis to analyze temperamental and executive functioning profiles of media multitaskers in early adolescence. Media multitasking is particularly intense in adolescence (Smahel et al., 2020), with implications for short- and long-term functioning (van der Schuur et al., 2015, 2020). Temperament and executive functioning are central for self-regulation and adaptation during adolescence (Rothbart et al., 2011; Blakemore & Choudhury, 2006; Atherton et al., 2019) and are related to media multitasking (van der Schuur et al., 2015; Rogobete et al., 2021, 2024). Participants were a group of early adolescents (11 - 14.5 years old). Community detection yielded 3 distinct groups of individuals, characterized by various combinations of media multitasking frequency, temperamental traits and executive functioning problems. Relevant similarities and differences have been identified between these groups using further quantitative analyses. Results are discussed in terms of the dynamics between temperament, executive functioning and media multitasking behavior during adolescence – an important period for the development of self-regulation and the formation of media habits. Importantly, this exploratory study offers preliminary evidence supporting the usefulness of community detection in complex network analysis for investigating the dynamics of media multitasking behavior.